2018
DOI: 10.1126/science.aat5749
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming normal human epithelial tissues to a common, lethal neuroendocrine cancer lineage

Abstract: The use of potent therapies inhibiting critical oncogenic pathways active in epithelial cancers has led to multiple resistance mechanisms including the development of highly aggressive, small cell neuroendocrine carcinoma (SCNC). SCNC patients have a dismal prognosis due in part to a limited understanding of the molecular mechanisms driving this malignancy and the lack of effective treatments. Here we demonstrate that a common set of defined oncogenic drivers reproducibly reprograms normal human prostate and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
227
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(250 citation statements)
references
References 50 publications
18
227
0
Order By: Relevance
“…The recent introduction of therapies that better target the androgen axis has led to a significant increase in frequency of castrate-resistant prostate cancer with neuroendocrine differentiation 8 . It has been shown that inactivation of the RB1 tumor suppressor gene increases cell plasticity along with the promotion of an aggressive neuroendocrine phenotype 19,27,32 . In castrated mice with combined Pten and Trp53 deficiency some prostate tumors arising from luminal cells had regions of highly proliferative cells with overt neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of therapies that better target the androgen axis has led to a significant increase in frequency of castrate-resistant prostate cancer with neuroendocrine differentiation 8 . It has been shown that inactivation of the RB1 tumor suppressor gene increases cell plasticity along with the promotion of an aggressive neuroendocrine phenotype 19,27,32 . In castrated mice with combined Pten and Trp53 deficiency some prostate tumors arising from luminal cells had regions of highly proliferative cells with overt neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of oncogenes required to transform cells to the most common prostate or lung cancer forms is not known. However, both primary prostate and lung epithelial cells can be transformed to small cell neuroendocrine carcinoma, suggesting that either a minority population of neuroendocrine cells are susceptible for transformation, or that both types of primary cells assume a neuroendocrine fate after transformation 43 .…”
Section: );mentioning
confidence: 99%
“…Emerging evidence suggests that t‐NEPC is derived from AdPC, and this transition can occur as a result of NE differentiation. Several studies have reported that AdPC and t‐NEPC tumors have similar genotypes (ie, somatic copy number, point mutations, and polyploidy), while their transcriptome, epigenome, and cellular morphologies differ . In recent studies, we have shown that a pre‐mRNA splicing factor, SRRM4, can drive NE differentiation to transform LNCaP AdPC cells into t‐NEPC tumors by reprogramming the transcriptome through alternative RNA splicing under ARPI .…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported that AdPC and t-NEPC tumors have similar genotypes (ie, somatic copy number, point mutations, and polyploidy), while their transcriptome, epigenome, and cellular morphologies differ. [5][6][7][8] In recent studies, we have shown that a pre-mRNA splicing factor, SRRM4, can drive NE differentiation to transform LNCaP AdPC cells into t-NEPC tumors by reprogramming the transcriptome through alternative RNA splicing under ARPI. 9 This report established a new NEPC cell model, called LnNE, which uses SRRM4-overexpressing LNCaP cells to create five generations of xenografts and cell models.…”
mentioning
confidence: 99%